ELICITATION TECHNIQUE AND ITS IMPACT ON COMMUNICATIVE COMPETENCE (An experiment Study Conducted at SMP Pasundan 1 Cimahi) - Kaswan, Kaswan (STKIP Siliwangi, 2014)
This study is inspired by the fact that the English teaching and learning is still dominated by the teacher centred approach. As a result, students’ communicative competence is below expectation. For that reason and another, the teacher should shift their teaching approach from the teacher centred approach to learner centred approach by using elicitation technique. The main objective of this study is to find out the impact of elicitation technique on students’ communicative competence. Accordingly, the research method used is quantitative research, or more specifically the quasi-experimental design with the Matching-Only Posttest-Only Control Group Design which consists of two classes (86 students) as the sample. Data analysis shows that the observed value of t (2.36) is bigger than the critical value of t (1.67). As a conclusion, the elicitation technique has a significant impact on students’ communicative competence.Keywords: teacher centred approach, communicative competence, elicitation, learner centred approach